Implementasi Program Paku Bumi dalam Konteks Penguatan Pendidikan Karakter di MIN 1 Kota Malang - Imroatul Fadliyah; Sa’dun Akbar; Muchtar Muchtar; Imroatul Fadliyah; Sa’dun Akbar (Universitas Negeri Malang, 2021)
Abstract: Character education is very important for students to be formed as early as possible. MIN 1 Malang City applies character education with a PAKU BUMI program. The objectives of this study are (1) the concept of the PAKU BUMI program; (2) the implementation of the PAKU BUMI program in strengthening character education; (c) character education values ​​embedded in students through the PAKU BUMI program; (d) supporting factors and inhibiting factors; (e) student behavior as a result of the implementation of the PAKU BUMI program.This research uses a qualitative approach with the type of case study research. Researchers as a key instrument. Data collection techniques by observation, interviews, and documentation. Data analysis includes data reduction, data presentation, drawing conclusions. The validity of the data using techniques of increasing persistence and triangulation techniques. In this study, researchers reveal and explain in detail the implementation of the PAKU BUMI program. The results of the study found that the PAKU BUMI program is an arrangement of the national curriculum of the Ministry of Religion, the vision and mission of madrasas, and circulars of the Ministry of Religion of Malang City with the aim of increasing the KI 1 and KI 2. The PAKU BUMI program is an intracurricular activity in accordance with presidential regulation number 87 2017 concerning strengthening character education. There are several activities from the PAKU BUMI program in strengthening character education through (a) fardhu prayers and sunnah prayers; (b) dhikr and prayers after prayers and daily prayers; (c) reading the Koran and memorizing juz 30; (d) spread greetings; (e) fasting in Ramadan and fasting sunnah; (f) morality; (g) life skills or life skills. The PAKU BUMI program is able to bring out unique and distinctive character values ​​in activities. In accordance with the provisions of the presidential regulation on strengthening character education. The PAKU BUMI program has an impact on the behavior of students who are honest, responsible, disciplined, and independent for themselves and those around them. Abstrak: Pendidikan karakter sangat penting bagi siswa dengan dibentuk sedini mungkin. MIN 1 Kota Malang menerapkan pendidikan karakter dengan sebuah program PAKU BUMI Tujuan penelitian ini untuk (1) konsep program PAKU BUMI; (2) implementasi program PAKU BUMI dalam penguatan pendidikan karakter; (c) nilai-nilai pendidikan karakter yang tertanam pada siswa melalui program PAKU BUMI; (d) faktor pendukung dan faktor penghambat; (e) perilaku siswa sebagai dampak implementasi program PAKU BUMI. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian studi kasus. Peneliti sebagai instrumen kunci. Teknik pengumpulan data dengan observasi, wawancara, dan dokumentasi. Analisis data meliputi reduksi data, penyajian data, menarik kesimpulan. Keabsahan data menggunakan teknik meningkatkan ketekunan dan teknik triangulasi. Pada penelitian ini peneliti mengungkapkan dan menjelaskan secara detail implementasi program PAKU BUMI. Hasil penelitian didapatkan bahwa program PAKU BUMI merupakan susunan dari kurikulum nasional Kementerian Agama, visi misi madrasah, dan surat edaran Kementerian Agama Kota Malang dengan tujuan untuk meningkatkan pada KI 1 dan KI 2. Program PAKU BUMI merupakan kegiatan intrakurikuler yang sesuai dengan peraturan presiden nomor 87 tahun 2017 tentang penguatan pendidikan karakter. Terdapat beberapa kegiatan dari program PAKU BUMI dalam penguatan pendidikan karakter melalui (a) shalat fardhu dan shalat sunnah; (b) dzikir dan doa setelah salat serta doa sehari-hari; (c) membaca al-quran dan hafalan juz 30; (d) menebar salam; (e) puasa Ramadhan dan puasa sunnah; (f) akhlakul karimah; (g) life skill atau kecakapan hidup. Program PAKU BUMI mampu memunculkan nilai-nilai karakter yang unik dan khas dalam kegiatan. Sesuai dengan ketetapan peraturan presiden tentang penguatan pendidikan karakter. Program PAKU BUMI berdampak pada perilaku siswa yang jujur, tanggung jawab, disiplin, dan mandiri untuk dirinya dan sekitarnya.